Gambaran Religiusitas Pada Wanita Pekerja Seks Di Organisasi Perubahan Sosial Indonesia Kota Banjarmasin - Sari, Aulia; Abidin, Muhammad Zainal; Imadduddin, Imadduddin (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
Prostitution or the practice of prostitution is a profession that is as old as human civilization, many people think that prostitution has existed since humans existed and continues to grow today. And the facts on the ground until now show that people still justify that PSK/WPS are always in a circle that seems far from religion, even though based on observations and interviews with researchers, there are some PSK/WPS who show their religiosity because they are separated from the work they are currently doing. Each individual has their respective levels of religiosity with levels that are not the same from one individual to another. Based on preliminary studies and previous research, it was found that female sex workers also knew about religiosity. Therefore, this study aims to find out how the picture of the religiosity of female sex workers in Indonesian social change organizations in the city of Banjarmasin. This study is a qualitative descriptive study, with a total of 3 subjects who came from members of Indonesian social change organizations. Data collection methods used are interview methods, observation methods and documentation methods. The results showed that the picture of the religiosity of female sex workers in the Indonesian social change organization in the city of Banjarmasin was that of the three subjects they strongly believed in religion and God.